Exotic signals of vectorlike quarks. (25th June 2018) - Dobrescu, Bogdan A; Yu, Felix
Abstract: Vectorlike fermions are an important target for hadron collider searches. We show that the vectorlike quarks may predominantly decay via higher-dimensional operators into a quark plus a couple of other standard model fermions. Pair production of vectorlike quarks of charge 2/3 at the LHC would then lead to a variety of possible final states, including t t ̄ + 4 τ, t b ̄ ν + 3 τ, t t ̄ + 4 μ, t b ̄ ν + 3 μ or t t ̄ + 4 b . Additional channels ( b b ̄ + 4 τ, 4 t + b b ̄, 6 b, etc) arise in the case of a vectorlike quark of charge −1/3. If the vectorlike quark decays into three light quarks, then the 3 j + 3 j signal is more difficult to observe, and the vectorlike quark mass is almost unconstrained by current searches.